Shifting faunal baselines through the Quaternary revealed by cave fossils of eastern Australia - Price, Gilbert J. (PeerJ, 2019)
Fossils from caves in the Manning Karst Region, New South Wales, Australia have long been known, but until now have never been assessed for their palaeontological significance. Here, we report on late Quaternary faunal records from eight caves in the region. Extinct Pleistocene megafaunal taxa are recognised in two systems and include giant echidnas (Tachyglossidae gen. et sp. indet.), devils (Sarcophilus laniarius), koalas (Phascolarctos stirtoni), marsupial ‘lions’ (Thylacoleo carnifex), and kangaroos (Macropus giganteus titan). Some caves contain skeletal remains of introduced exotics such as sheep and dogs, but also provide a rich record of small-bodied native species including Eastern Bettongs (Bettongia gaimardi), Eastern Chestnut Mice (Pseudomys gracilicaudatus), and White-footed Rabbit Rats (Conilurus albipes). These endemics are either locally extirpated or have suffered total extinction in the historic period. Their skeletal and dental remains were recorded as unmineralised surface specimens in the caves, indicating that they are recent in age. Extant populations have never been recorded locally, thus, their probable loss from the region in historic times had gone unnoticed in the absence of palaeo-evidence. Our findings suggest that the supposed habitat tolerances of such species have been substantially underestimated. It is highly likely that modern populations have suffered niche contraction since the time of European colonisation of the continent. The local extirpations of several species of digging mammal has likely led to decreased functionality of the current ecosystem.